Malignant Odontogenic Tumours: A Systematic Review of Cases Reported in Literature - Marin, Constanza; Dave, Manas; Hunter, Keith D. (Frontiers in Oral Health, 2021)
Background: Malignant odontogenic tumours (MOTs) arise either de novo from the tooth forming tissues, their developmental residues or from existing odontogenic epithelial or mesenchymal neoplasms in the jaws. Their management requires extensive surgery due to their infiltrative nature and risk of metastasis. There is a need to understand the clinical and pathological features of MOTs to inform both treatment algorithms and prognostication. This is an area of diagnostic pathology which presents substantial difficulties in diagnosis, compounded by inconsistent use of terminology. Thus, this systematic review aimed to describe the clinical and pathological features of MOTs with a view to consolidating the literature and defining problematic areas in diagnosis and classification. Methods: An electronic database search was conducted in Web of Science, PubMed/Medline, and Embase. Additionally, the grey literature and reference lists of selected papers searched for completeness. Nine hundred and sixty articles were initially identified. Following removal of duplicates and application of inclusion/exclusion criteria, 312 articles were included for qualitative analysis. Results: The 312 articles encompassed a total of 507 patients with most lesions located within the mandible (74.3%). The most common first histological diagnosis was ameloblastic carcinoma (25.7% of all diagnoses), but there is considerable variation in how and when various diagnostic terms are used, and several misdiagnoses were reported. An initial benign diagnosis was made in 24.7% of patients, followed by a later malignant diagnosis and in this sub-group, the most common benign first diagnosis was ameloblastoma (42.4%). Cervical lymph nodes were the most common site of metastasis (9.3% of patients). With respect to distant metastasis (DM), the lungs were the most common organ affected (11.2% of DM patients) with metastasising ameloblastoma the most commonly reported tumour which metastasised to the lungs. Overall, 26.8% of patients developed recurrence. Conclusion: Overall, the quality of the literature on MOTs is poor. This review of the literature has highlighted variations in diagnostic terms and criteria which has resulted in areas of confusion with potential for misdiagnosis. This consolidation of primary data has identified key areas for targeted research including further discussion on the malignant potential of ameloblastoma.